2013
DOI: 10.1155/2013/585439
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobiology and Treatment of Restless Legs Syndrome

Abstract: Background: Restless legs syndrome (RLS) is a relatively common neurological disorder affecting sleep and health-related quality of life. Neuroimaging studies, autopsy investigations and experimental studies using animal models have been conducted to investigate the potential causes of RLS, resulting in the generation of multiple pathophysiological hypotheses. Methods: This paper reviews the neurobiology and pharmacotherapy of RLS, with a critical analysis of the heterogeneity and methodological limitations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…The scores of individual questions are aggregated to yield a total score ranging from 0 to 40. Based on the IRLS score, RLS was graded as mild (0-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and very severe (31-40). All the subjects diagnosed with RLS were provided the standard-of-care management by the neurologist (VP) in the research team [22].…”
Section: Methodsmentioning
confidence: 99%
“…The scores of individual questions are aggregated to yield a total score ranging from 0 to 40. Based on the IRLS score, RLS was graded as mild (0-10), moderate (11)(12)(13)(14)(15)(16)(17)(18)(19)(20), severe (21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and very severe (31-40). All the subjects diagnosed with RLS were provided the standard-of-care management by the neurologist (VP) in the research team [22].…”
Section: Methodsmentioning
confidence: 99%
“…13,[63][64][65] A dopaminergic deficiency has also been implicated in the pathophysiology of depression. [66][67][68] Dopamine-containing circuits in the central nervous system are thought to be involved in the regulation of motivation, concentration, and the ability to experience pleasure, all 3 of which are impaired in patients with depression.…”
Section: Although the Neurobiological Pathways Involved In Rlsmentioning
confidence: 99%
“…Headache, fatigue, sleep disturbances, depression and anxiety are common in patients with FM and/or RLS and quality of life is adversely affected (10,34,35,45,46). Looking at the data from our study, the addition of FM symptoms on RLS symptoms causes significantly worse responses to questions ("How do you think your overall health is?"…”
Section: Discussionmentioning
confidence: 80%
“…Although the pathogenesis of RLS is not fully understood, a decreased amount of iron in the central nervous system and perturbation in the dopaminergic system were thought to play important roles (34). It is suggested that dopamine activity decreases at night as a result of postsynaptic receptor desensitization due to hyperdopaminergia (35). The use of dopamine-containing drugs in the treatment supports this hypothesis (36,37).…”
Section: Discussionmentioning
confidence: 99%